Ambient-temperature oxidative coupling of methane in an electric field by a cerium phosphate nanorod catalyst. Issue 28 (26th February 2019) - Sato, Ayaka; Ogo, Shuhei; Kamata, Keigo; Takeno, Yuna; Yabe, Tomohiro; Yamamoto, Tomokazu; Matsumura, Syo; Hara, Michikazu; Sekine, Yasushi
Abstract : The application of an electric field to a CePO4 nanorod catalyst enabled ambient-temperature oxidative coupling of methane to C2 hydrocarbons. Abstract : CePO4 nanorods with uniform surface Ce sites could work as a durable catalyst and showed the highest C2 yield of 18% in an electric field without the need for external heating, which was comparable to that reported for high-performance catalysts at high temperature (>900 K).